Interactive Effects of the COMT Gene and Training on Individual Differences in Supervisory Control of Unmanned Vehicles. (June 2014) - Parasuraman, Raja; Kidwell, Brian; Olmstead, Ryan; Lin, Ming-Kuan; Jankord, Ryan; Greenwood, Pamela
Objective: We examined whether a gene known to influence dopamine availability in the prefrontal cortex is associated with individual differences in learning a supervisory control task. Background: Methods are needed for selection and training of human operators who can effectively supervise multiple unmanned vehicles (UVs). Compared to the valine (Val) allele, the methionine (Met) allele of the COMT gene has been linked to superior executive function, but it is not known whether it is associated with training-related effects in multi-UV supervisory control performance. Method: Ninety-nine healthy adults were genotyped for the COMT Val158Met single nucleotide polymorphism (rs4680) and divided into Met/Met, Val/Met, and Val/Val groups. Participants supervised six UVs in an air defense mission requiring them to attack incoming enemy aircraft and protect a no-fly zone from intruders in conditions of low and high task load (numbers of enemy aircraft). Training effects were examined across four blocks of trials in each task load condition. Results: Compared to the Val/Met and Val/Val groups, Met/Met individuals exhibited a greater increase in enemy targets destroyed and greater reduction in enemy red zone incursions across training blocks. Conclusion: Individuals with the COMT Met/Met genotype can acquire skill in executive function tasks, such as multi-UV supervisory control, to a higher level and/or faster than other genotype groups. Application: Potential applications of this research include the development of individualized training methods for operators of multi-UV systems and selecting personnel for complex supervisory control tasks.